2022
DOI: 10.2147/ndt.s381461
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Disorder, Suicidal Behavior, Substance Use, and Sexual Victimization Among Adolescent Girls Aged 10-19 Years Living Under Ethnic-Based Civil War in Ethiopia

Abstract: Background Posttraumatic stress disorder (PTSD) is a chronic, impairing mental disorder that develops after exposure to a traumatic event. Despite many factors putting adolescent girls at risk of PTSD, little is known about the prevalence and how adolescent girls cope with the PTSD burden. So, this study aimed to investigate the prevalence of PTSD and associated factors among adolescent girls in three selected towns in Southwest Ethiopia. Methods A community-based cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
(79 reference statements)
1
0
0
Order By: Relevance
“…The study found that individuals who currently chewed khat were 2.21 times more likely to develop PTSD compared to those who did not use khat. This finding is consistent with previous studies conducted in Southwestern Uganda ( 50 ), Ethiopia ( 51 ), China ( 52 ), and Somalia ( 53 ). Substance abuse, like khat use, can hinder the body’s natural ability to cope with trauma, increase physiological arousal, and worsen PTSD symptoms ( 54 ).…”
Section: Discussionsupporting
confidence: 93%
“…The study found that individuals who currently chewed khat were 2.21 times more likely to develop PTSD compared to those who did not use khat. This finding is consistent with previous studies conducted in Southwestern Uganda ( 50 ), Ethiopia ( 51 ), China ( 52 ), and Somalia ( 53 ). Substance abuse, like khat use, can hinder the body’s natural ability to cope with trauma, increase physiological arousal, and worsen PTSD symptoms ( 54 ).…”
Section: Discussionsupporting
confidence: 93%